Gas-blasting nanocapsules to accelerate carboplatin lysosome release and nucleus delivery for prostate cancer treatment - Shunli Fu; Shuang Liang; Dandan Jiang; Rui Yang; Zipeng Zhang; Lili Chang; Xinke Zhang; Yongjun Liu; Na Zhang (Elsevier, 2021)
To improve therapeutic effect and reduce severely side effects of carboplatin (CBP), the gas-generating nanocapsules were developed to accelerate CBP lysosome release and nucleus delivery. CBP/SB-NC was prepared by co-loading CBP and NaHCO3 (SB) in nanocapsules using w/o/w emulsification solvent evaporation. They exhibited vesicle-like spherical morphology, uniform particle size and negative zeta potential. Reaching the tumor site with a relatively high concentration is the first step for CBP delivery and the results showed that CBP/SB-NC could effectively increase drug accumulation at tumor site. After that, the drug delivery carriers need to be internalized into tumor cells and the in vitro cellular uptake ability results showed CBP/SB-NC could be internalized into RM-1 cells more efficient than CBP solution. After internalized by RM-1 cells, the gas-blasting release process was tested in acid environment. It was demonstrated that 5 mg/ml NaHCO3 was optimal to achieve pH-responsive gas-blasting release. In vitro release results showed that CBP significantly rapid release in acid environment (pH 5.0) compared to neutral pH (pH 7.4) (P < 0.05). Meanwhile, TEM and the change of the concentration of H+ results exhibited that the explosion of CBP/SB5-NC was more easily happened in lysosome acid environment (pH 5.0). The blasting release can accelerate CBP lysosome release to cytoplasm. Furthermore, the nucleus delivery results showed CBP/SB5-NC can promote pH-triggered rapid nucleus delivery. And the results of Pt-DNA adduct assay showed that the binding efficiency between CBP and DNA of CBP/SB5-NC was higher than CBP solution. At last, in vitro and in vivo anti-tumor efficacy proved that CBP/SB5-NC could enhance anti-tumor activity for prostate cancer therapy. CBP/SB5-NC also showed superior safety in vitro and in vivo by hemolysis assay and histopathological study. All of the results demonstrate that CBP/SB5-NC would be an efficient gas-blasting release formulation to enhance prostate cancer treatment.